Enhancing Internal Learning in Teams: The Role of Network Centrality and Psychological Capital of Undergraduate Students - Geremias, Rosa Lutete; Lopes, Miguel Pereira; Soares, André Escórcio (Frontiers in Psychology, 2020)
Abstract This study aims to analyze the mediating role of psychological capital in the relationship between network centrality and internal learning in teams. A questionnaire was administered to 480 undergraduate students to test this relationship. The results confirmed the positive relationship between network centrality and internal learning in teams, and a mediating role of psychological capital in the relationship between student network centrality and internal learning in teams. This study suggests that it is important to promote centrality in advice networks among undergraduate students. In addition, this study might raise awareness among students, teachers, and public policymakers about the need to promote a socially responsible environment in Higher Education Institutions.